2006
DOI: 10.2214/ajr.04.0942
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Use of a Saline Chaser to Reduce the Volume of Contrast Medium in Abdominal CT

Abstract: In MDCT, reducing the amount of contrast medium does not affect aortic enhancement in the early arterial phase but decreases hepatic enhancement at the portal phase. The saline chaser technique had no influence on the phases studied. Greater than 1.5 mL/kg reduction in the dose of contrast medium followed by saline flushing may not be advisable for liver CT in low- and medium-weight patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Since the late 1990s various clinical reports have been published on saline-chaser technique for computed tomography (CT) angiography of the head and neck, thorax, and abdomen [1][2][3][4][5][6][7]. The saline-chaser technique results in greater efficiency of the administered contrast medium dose by avoiding accumulation of the contrast medium in the injection tubing and in the venous system between the injection site and the atrium of the right heart [4,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the late 1990s various clinical reports have been published on saline-chaser technique for computed tomography (CT) angiography of the head and neck, thorax, and abdomen [1][2][3][4][5][6][7]. The saline-chaser technique results in greater efficiency of the administered contrast medium dose by avoiding accumulation of the contrast medium in the injection tubing and in the venous system between the injection site and the atrium of the right heart [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…The saline-chaser technique results in greater efficiency of the administered contrast medium dose by avoiding accumulation of the contrast medium in the injection tubing and in the venous system between the injection site and the atrium of the right heart [4,7]. The increased contrast medium efficiency can be used either to obtain enhancement or to reduce contrast medium volume.…”
Section: Introductionmentioning
confidence: 99%
“…Saline flush has been used to reduce the contrast medium dose while maintaining the enhancement of the aorta [12][13][14] and iliac arteries [15]. Saline flush is also used in coronary CT angiography to increase the coronary enhancement [3].…”
Section: Discussionmentioning
confidence: 99%
“…Saline flush is also used in imaging the aorta [10][11][12] and carotid arteries [13] . A previous study showed that approximately 10 to 20 mL of contrast medium remained in the brachial vein or the superior vena cava without saline flush [14] .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that approximately 10 to 20 mL of contrast medium remained in the brachial vein or the superior vena cava without saline flush [14] . By pushing this residual contrast medium into the central venous system, a saline flush could achieve a reduction of 12 mL [15] or 10% dose of contrast medium [3,11] with maintained arterial enhancement in the arterial phase. Other studies showed that saline flush increased the enhancement of coronary arteries [3] and aorta [10] by 10%.…”
Section: Discussionmentioning
confidence: 99%